Hacia una formación integral desde la dimensión comunicativa (2021)
Communication is a fundamental aspect in che life of man. le allows him to become pare of a communicy and to build sociecy. This dimension has a fundamental role in che school due to che importance of developing communica tive skills in chese socialization spaces, which allow indi viduals to interact and perform cheir diverse roles in che contexts chey develop. This is essential for all societies to move forward. For chis reason, che communicative dimen sion's labour of Saint Thomas Aquinas School is required for aware and critica! citizens formation who concribuce to che historical progression of che country.